Answer:
=![10n^4 - 3n^3 -20](https://tex.z-dn.net/?f=10n%5E4%20-%203n%5E3%20-20)
Step-by-step explanation:
Given that:
=(1 - 3n3 + 2n4) + (8n4 – 13 – 7)
By opening the brackets we get:
= 1-3n3 +2n4 +8n4 -13 -7
By adding like terms: Constants into constants and variables with same powers of x.....
= -20 - 3n3 +10n4
So by arranging the answer in decreasing order of powers of x:
=![10n^4 - 3n^3 -20](https://tex.z-dn.net/?f=10n%5E4%20-%203n%5E3%20-20)
I hope it will help you!
Simplifying 3y + 6 = 18.9 Reorder the terms: 6 + 3y = 18.9 Solving 6 + 3y = 18.9 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3y = 18.9 + -6 Combine like terms: 6 + -6 = 0 0 + 3y = 18.9 + -6 3y = 18.9 + -6 Combine like terms: 18.9 + -6 = 12.9 3y = 12.9 Divide each side by '3'. y = 4.3 Simplifying y = 4.3
Answer: Choice B
(x-1)(x^3+x^2+5x+6)
==========================================
Explanation:
The 1 in the upper left box means that x = 1 is a root of the original polynomial.
So this means x-1 is a factor of the original polynomial.
This is because x = 1 leads to x-1 = 0 after subtracting 1 from both sides.
-----------------
The 0 in the last position of the bottom row shows we got a remainder of 0.
Getting a remainder 0 tells us that (x-1) is a factor of the polynomial. This synthetic division table confirms our initial guess.
The other values in that bottom row (1, 1, 5, 6) form coefficients to the polynomial 1x^3+1x^2+5x+6, or simply x^3+x^2+5x+6
-------------------
So we know that (x-1) and (x^3+x^2+5x+6) are factors
Meaning that,
x^4+4x^2+x-6 = (x-1)(x^3+x^2+5x+6)
You can confirm this by expanding out the right hand side (distribution rule).
$18 is the rounded dollar to $18.48
I hope this helps you
Area=height.base/2
Area =2. (x+1)/2
Area =x+1